PENGARUH EMPLOYEE SATISFACTION TERHADAP PROFITABILITY PADA HOTEL BERBINTANG TIGA DI SURABAYA - Kurniawan, Kurniawan (Business Accounting Review, 2013)
The desire to be able to grow makes the company try to compete by providing the best service to its customers, so that the company can obtain an increase in profit. In the effort to provide the best service, it wonât be apart from the effort of the employees, so the employeeâs satisfaction become a mandatory requirement that must be fulfilled by the company management. Same circumstances may also occur in the service of the hotel business. Based on those phenomenas, this study will attempt to demonstrate the effectiveness of the Balanced Scorecard on Three-Star Hotel in Surabaya. The researchâs objects were 5 Three-Star hotels in Surabaya by taking sample of 8 employees in each division and 8 customers. The results of the analysis is using Partial Least Square.